ISO 9001 and IWA-2 Quality Management System in Education - Fery Wibowo (Institute of Accounting Research and Novation (IARN), 2023)
This study observes that an institution will continue to exist if its products can provide satisfaction to customers, especially in education. The purpose of this research is to maintain existence, guarantee customer satisfaction is needed and a continuous improvement process must always be carried out and educational institutions that are always in demand by the community are those that are good at managing existing resources, accountable, quality, and able to compete with other institutions and make their students continuing further education or entering the world of work with science and technology as well. The method used in this research is qualitative method